What factors affect team members’ evaluation of collaboration in medical teams? - Kämmer, Juliane E.; Ehrhard, Simone; Kunina-Habenicht, Olga; Weber-Schuh, Sabine; Hautz, Stefanie C.; Birrenbach, Tanja; Sauter, Thomas C.; Hautz, Wolf E. (Frontiers in Psychology, 2023)
Perceived teamwork quality is associated with numerous work-related outcomes, ranging from team effectiveness to job satisfaction. This study explored what situational and stable factors affect the perceived quality of teamwork during a specific team task: when a medical team comprising a senior (supervisor) and a junior (trainee) physician diagnoses a patient. During a field study in an emergency department, multisource data describing the patients, the diagnosing physicians, and the context were collected, including physicians’ ratings of their teamwork. The relationships between perceived teamwork quality and situational (e.g., workload) and stable (e.g., seniority) factors were estimated in a latent regression model using the structural equation modeling (SEM) approach. Across the N = 495 patients included, SEM analyses revealed that the patient-specific case clarity and urgency influenced the perceived teamwork quality positively, whereas the work experience of the supervisor influenced the perceived teamwork quality of both supervisor and trainee negatively, albeit to different degrees. Our findings shed light on the complex underpinnings of perceived teamwork quality, a performance-relevant factor that may influence work and organizational effectiveness in healthcare settings.